Increasing Student’s Mathematical Creative Thinking Ability Through Realistic Mathematics Education (RME) and Connecting, Organizing, Reflecting, Extending (CORE) Learning Models - Susilowaty, Nora; Risamasu, Mary (8ISC Proceedings: Arts and Education; 8ISC Proceedings: Arts and Education, 2022)
A superior level of thinking ability that needs to be developed in math study is creative thinking ability. Creative thinking ability needs to be acquired and developed by students in order to be able to express many ideas in problem-solving. Math subjects fall into definite science that requires more creative thinking than memorization. The research aims to see if there is a difference between the student who gets the RME learning model and the student who gets the CORE learning model. The research was carried out at the public school of 2 Parongpong, West Bandung. These samples are class VIII B as a class that gets Realistic Mathematics Education (RME) learning models and VIII C class that gets Connecting, Organizing, Reflecting, Extending (CORE) learning models. The instruments used in this research were test and non-test instruments. The test instrument was a test of mathematical creative thinking ability consisting of pre-test and post-test, while non-test instruments consisted of student responses questionnaire about learning models. The data were analyzed using the Shapiro-Wilk test and Mann-Whitney test. Research shows that: The early creative ability of mathematical thinking students who earn lessons with RME models and CORE models are in low categories because their initial skill average is below 50%. It’s different after being given the learning treatment. The enhanced students’ creative thinking abilities in both classes are in moderate categories, and there is no difference in the enhancement of mathematical creative thinking ability between students who had the RME model and students that used the CORE learning model. Students’ responses indicate that they really love learning with RME and CORE models. Keywords : Realistic Mathematics Education (RME), Connecting, Organizing, Reflecting, Extending (CORE), Mathematical Creative Thinking Ability